Comparison of the Prevalence of Chronic Obstructive Pulmonary Disease Diagnosed by Lower Limit of Normal and Fixed Ratio Criteria - Hwang, Yong Il; Kim, Chang Hwan; Kang, Hye-Ryun; Shin, Taerim; Park, Sang Myeon; Jang, Seung Hun; Park, Yong Bum; Kim, Cheol Hong; Kim, Dong-Gyu; Lee, Myung Goo; Hyun, In-Gyu; Jung, Ki-Suck (Journal of Korean medical science, 2009)
The Global Initiative of Chronic Obstructive Lung Disease (GOLD) guidelines define chronic obstructive pulmonary disease (COPD) in subjects with FEV(1)/FVC <0.7. However, the use of this fixed ratio may result in over-diagnosis of COPD in the elderly, especially with mild degree of COPD. The lower limit of normal (LLN) can be used to minimize the potential misclassification. The aim of this study was to evaluate the impact of different definitions of airflow obstruction (LLN or fixed ratio of FEV(1)/FVC) on the estimated prevalence of COPD in a population-based sample. We compared the prevalence of COPD and its difference diagnosed by different methods using either fixed ratio (FEV(1)/FVC <0.7) or LLN criterion (FEV(1)/FVC below LLN). Among the 4,816 subjects who had performed spirometry, 2,728 subjects met new ATS/ERS spirometry criteria for acceptability and repeatability. The prevalence of COPD was 10.9% (14.7% in men, 7.2% in women) by LLN criterion and 15.5% (21.8% in men, 9.1% in women) by fixed ratio of FEV(1)/FVC among subjects older than 45 yr. The difference of prevalence between LLN and fixed ratio of FEV(1)/FVC was even higher among subjects with age >/=65, 14.9% and 31.1%, respectively. In conclusion, the prevalence of COPD by LLN criterion was significantly lower in elderly compared to fixed ratio of FEV(1)/FVC. Implementing LLN criterion instead of fixed ratio of FEV(1)/FVC may reduce the risk of over-diagnosis of COPD in elderly people.